2020
DOI: 10.1161/hypertensionaha.120.15554
|View full text |Cite
|
Sign up to set email alerts
|

CAR (CARSKNKDC) Peptide Modified ReNcell-Derived Extracellular Vesicles as a Novel Therapeutic Agent for Targeted Pulmonary Hypertension Therapy

Abstract: In recent years, mesenchymal stem cells (MSCs)–derived extracellular vesicles (EVs) are emerging as a potential therapeutic agent for pulmonary hypertension (PH). However, the full realization of MSCs–derived EVs therapy has been hampered by the absence of standardization in MSCs culture and the challenges of industrial scale–up. The study was to exploit an alternative replacement for MSCs using currently commercialized stem cell lines for effective targeted PH therapy. ReNcell VM—a human neural stem cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…The expression of miR-100-5p is decreased by hypoxia. EVs derived a human neural stem cell line that inhibits hypoxia-induced proliferation and migration through EV miR-100-5-p in pulmonary artery smooth muscle cells ( Wang et al, 2020 ). Hromadnikova et al found that downregulation of miR-100-5p was associated with gestational hypertension and preeclampsia ( Hromadnikova et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-100-5p is decreased by hypoxia. EVs derived a human neural stem cell line that inhibits hypoxia-induced proliferation and migration through EV miR-100-5-p in pulmonary artery smooth muscle cells ( Wang et al, 2020 ). Hromadnikova et al found that downregulation of miR-100-5p was associated with gestational hypertension and preeclampsia ( Hromadnikova et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results of the CCK-8, wound healing and Transwell assays demonstrated that overexpression of miR-100 inhibited the proliferation, migration and invasion of breast cancer cells, respectively. miR-100 has been reported to play an important role in diseases, including atherosclerosis (16), acute lung injury (17), pulmonary hypertension (18), childhood acute lymphoblastic leukemia (19) and osteoarthritis of the temporomandibular joint (20). In addition, miR-100 has been suggested to serve as a diagnostic and therapeutic biomarker in epithelial ovarian cancer (8) and gastric and esophageal cancers (9).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate homing of the CAR peptide to OIR neovasculature at the peak of angiogenesis. More recently, studies have demonstrated that the CAR peptide also homes to diseases with a clear inflammatory component such as PAH [29,34,[38][39][40][41][42][43][44]47,48], vascular (aorta) aneurysms [35], muscular dystrophies [37] and myocardial infarction [49]. Due to its homing and tissue penetrating capabilities, CAR peptide has been used as a targeting device for a large number of different therapeutics in different experimental pulmonary disease models [29,34,[38][39][40][41][42][43][44]47].…”
Section: Discussionmentioning
confidence: 99%